Hydrology and Soil Manipulations of Iron‐Rich Ditch Mesocosms Provide Little Evidence of Phosphorus Capture within the Profile. Issue 3 (1st May 2017) - Ruppert, David E.; Needelman, Brian A.; Kleinman, Peter J.A.; Rabenhorst, Martin C.; Momen, Bahram; Wester, David B.
Abstract : Agricultural drainage ditches function as first‐order streams and affect nutrient management. Soil mesocosms from a ditch featuring a vertical (increasing upward) gradient in iron (Fe) and phosphorus (P) were subjected to hydraulic and soil treatments. These manipulations mimicked aspects of dredging and controlled drainage and inspected the soil release and retention of P. Treatments did not remove P from simulated groundwater. Throughput water either gained in P (lack of dredging, especially under Fe‐reducing conditions) or had P concentrations indistinguishable from input water (dredging). Undredged mesocosms, when Fe‐reducing, released Fe and P simultaneously. Simultaneous release of P and Fe from our Fe‐reducing mesocosms indicates a mechanism whereby P capture occurs by Fe precipitation upon emergence to aerated surficial waters. Upwelling and surficial phases of ditch hydrology and the lowering of the ditch surface on dredging complicate interpretation of traditional means of describing ditch P retention and release. Core Ideas: Fe‐based P capture occurs as Fe oxidizes upon emergence at the ditch surface. At our site, P capture is not based on properties of in‐place soil material. Many common techniques assume P capture by in‐place soil materials. At our site, P capture appears to occur simultaneous to soil formation.